Fungi associated with leaves of Sonneratia apetala Buch. Ham and Sonneratia caseolaris (L.) Engler from Rangabali coastal zone of Bangladesh (Dhaka University Journal of Biological Sciences, 2018)
A total of six species and one genus of fungi associated with black leaf spot of Sonneratia apetala Buch. Ham (Kewra); and anthracnose and small leaf spot of S. caseolaris (L.) Engler (Choila) were isolated following “Tissue planting” method. The fungi associated with black spot of S. apetala were Aspergillus fumigatus Fresenius, Colletotrichum lindemuthianum (Sacc. & Magn.) Br. & Cav., Pestalotiopsis guepinii (Desm.) Stey. and Phoma betae Frank. Anthracnose of S. caseolaris showed the association of A. fumigatus and P. guepinii. The fungi associated with leaf spot of S. caseolaris were Curvularia fallax Boedijn, Fusarium Link, Penicillium digitatum (Pers.) Sacc. and P. betae. Frequency percentage of association of P. guepinii was highest (74.10) in black spot of S. apetala whereas the same fungus showed highest frequency percentage (85.70) in case of anthracnose of S. caseolaris. Phoma betae showed highest frequency percentage (60.00) in leaf spot of S. caseolaris. Phoma betae is first time recorded from Bangladesh.Dhaka Univ. J. Biol. Sci. 27(2): 155-162, 2018 (July)